Adequação a fundos imobiliários da fórmula mágica para ações de Joel Greenblatt - Kruger, Gustavo Corazzari [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The present work demonstrates an adaptation model of the “Magic Formula” for stock picking proposed by Joel Greenblatt in the book published in 2006 “The Little Book That Beats The Market” to the equivalent of Real Estate Investment Trusts (Fundos de Investimentos Imobiliários) in the brazilian financial market and the preliminary results of the application of this adapted formula. Based on two factors of the analyzed assets (return on invested capital - ROIC - and price to earnings ratio - P/E), the formula seeks to rank them to identify, in a simple way, assets with high efficiency and solid fundamentals, but that are being traded at attractive prices in the market. Similarly to the 16 years in which it was applied and studied by Greenblatt in the stock market of the USA (from 1988 to 2004), the methodology proved to be applicable and extremely promising to analyze Real Estate Investment Funds in the brazilian financial market. At the end of the analysis period (108 days, a period too short to infer definitive conclusions in a work involving the Financial Market), the portfolio assembled according to the magic formula showed profitability (including appreciation of the shares and earnings received) of 3.50%, while the portfolio formed by the other constituent assets of the study universe obtained a return of -0.19% and a portfolio composed of the 10 FIIs that held the largest participation in IFIX in October 2020 returned -0.37%. The data used in the study were obtained through information provided by BM&FBOVESPA, the results and reports released by the analyzed Funds and through the ClubeFii website database.

O presente trabalho apresenta um modelo de adaptação da “Fórmula Mágica” de análise de ações proposta por Joel Greenblatt no livro publicado em 2006 “The Little Book That Beats The Market” (“O Mercado De Ações Ao Seu Alcance” ou, em tradução livre, “O Pequeno Livro Que Bate O Mercado”) a Fundos de Investimentos Imobiliários (FIIs) e os resultados preliminares de sua aplicação. Baseando-se em dois indicadores técnicos dos ativos analisados (retorno sobre capital investido - ROIC - e preço sobre lucro - P/L), a fórmula busca ranquear-los para identificar, de maneira simples, ativos com alta eficiência e fundamentos sólidos, mas que estejam sendo negociadas a preços mais baixos no mercado. Assim como nos 16 anos em que foi aplicada e estudada por Greenblatt no mercado de ações (de 1988 a 2004), a metodologia se demonstrou aplicável e extremamente promissora para se analisar também Fundos de Investimentos Imobiliários. Ao final do período de análise (de 108 dias, um período demasiadamente curto para inferir conclusões definitivas em um trabalho que envolva o Mercado Financeiro), a carteira montada de acordo com a fórmula mágica apresentou rentabilidade (incluindo valorização das cotas e proventos recebidos) de 3,50%, enquanto a carteira formada pelos outros ativos constituintes do universo de estudo obteve retorno de -0,19% e uma carteira composta pelos 10 FIIs que detinham maior participação no IFIX em Outubro de 2020 apresentou rentabilidade de -0,37%. Os dados utilizados no estudo foram obtidos através de informações disponibilizadas pela BM&FBOVESPA, pelos resultados e informes divulgados pelos próprios Fundos analisados e por meio do banco de dados do site ClubeFii.
Adaptation model of the “Magic Formula” proposed by Joel Greenblatt to the equivalent of real estate investment trusts in the brazilian financial market
Keywords: Mercado financeiro; Fórmula mágica para ações; Metodologias de stock picking; Fundos de investimentos imobiliários